External shocks and the public sector: towards a quantitative approach - Urrunaga, Roberto (1991)
It is too much obvious that the Peruvian economy has suffered an erratic evolution. This article stresses the hypothesis that when external shocks occur, they have important effects on the economy and on its public sector. In order to test that hypothesis, the author uses a short term macroeconomic model that takes into account the public sector role and its fiscal policy. Then, the goal of this paper is to provide empirical evidence through the estimation of the external shocks effects and through the estimation of the government alternative responses to alleviate the perverse effects.